2013
DOI: 10.28945/1812
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ways to Use Facebook at the University Level: A Delphi Study

Abstract: Social networking sites have experienced tremendous growth and have become an integral part of the daily lives of a large portion of the population, both in the United States, as well as worldwide. Whereas a vast majority of university students log in to Facebook every day, both research and implementation of Facebook as a learning tool in higher education is lacking. This study investigates the question, "How can Facebook be used to enhance educational experiences beyond the traditional classroom?" To facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Second, social networking sites will provide much greater support for multimedia formats than traditional learning management system. Third, through the creation of personal profiles, students can potentially identify others with similar interests, leading to collaborative learning opportunities (Magro et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, social networking sites will provide much greater support for multimedia formats than traditional learning management system. Third, through the creation of personal profiles, students can potentially identify others with similar interests, leading to collaborative learning opportunities (Magro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the universal nature of Facebook, some have reported that it is used primarily for social and daily activities but rarely used by university students for educational purposes (Akyıldı and Argan, ; Magro et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students studying the subject are typically quite young, with an average age in our study sample 19.60 years, often completing the subject in their first year of study. This provides insights into recently commencing and continuing students' SNS use, who are very much immersed in a world of social networking (Hew, 2011;Kaya & Bicen, 2016;Magro, Sharp, Ryan, & Ryan, 2013).…”
Section: Contextmentioning
confidence: 99%